Keanekaragaman Serangga Hama dan Musuh Alami pada Lahan Pertanaman Kedelai di Kecamatan Balong-Ponorogo - INDRIYA RADIYANTO; MOCHAMMAD SODIQ; NOENG M. NURCAHYANI (Jurnal Entomologi Indonesia, 2010)
The study aims to determine the presence of pests and natural enemies on soybean plants and to study the effect of insecticides on the diversity. Methods for observation of insects was done by using different type of traps i.e. yellow pan trap, pitfall trap, light trap, sweeping net and direct observation (visual). The presence of pests and natural enemies of soybean plants on plots without insecticide was lower than on the plots that was treated with insecticide. Composition of the population of pests found in soybean plots that were not treated with insecticide were dominated by Aphis sp. followed by Phaedonia inclusa, Riptortus linearis, Nezara viridula and Ophiomyia phaseoli. Composition of the population of natural enemies (predators) found in soybean cropps that were not treated with insecticide was family Coccinellidae followed by Syrphidae, Chrysopidae, Mantidae and Oxyopidae. The highest composition of natural enemies (parasites) found in treated and untreated soybean plots were family Braconidae then followed by family Ichneumonidae.